2007
DOI: 10.1037/0022-3514.92.4.631
|View full text |Cite
|
Sign up to set email alerts
|

The BIAS map: Behaviors from intergroup affect and stereotypes.

Abstract: In the present research, consisting of 2 correlational studies (N = 616) including a representative U.S. sample and 2 experiments (N = 350), the authors investigated how stereotypes and emotions shape behavioral tendencies toward groups, offering convergent support for the behaviors from intergroup affect and stereotypes (BIAS) map framework. Warmth stereotypes determine active behavioral tendencies, attenuating active harm (harassing) and eliciting active facilitation (helping). Competence stereotypes determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

118
2,188
12
34

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,545 publications
(2,352 citation statements)
references
References 81 publications
118
2,188
12
34
Order By: Relevance
“…Cuddy et al (2007) found that perceived warmth of a group correlated with behavioral tendencies of helping, presumably mediated by pity, while perceived incompetence correlated with tendencies to neglect. This observation, once again, highlights the ambivalent nature of attitudes towards older adults.…”
Section: Neglect and Social Exclusionmentioning
confidence: 99%
“…Cuddy et al (2007) found that perceived warmth of a group correlated with behavioral tendencies of helping, presumably mediated by pity, while perceived incompetence correlated with tendencies to neglect. This observation, once again, highlights the ambivalent nature of attitudes towards older adults.…”
Section: Neglect and Social Exclusionmentioning
confidence: 99%
“…Thus, in organizational contexts, perceptions of competence, and not warmth, should more strongly dictate behavioral responses toward outgroups. The Behaviors from Intergroup Affect and Stereotypes (BIAS) Map (Cuddy et al, 2007) is an extension of the SCM that links warmth and competence stereotypes to specific behaviors. The BIAS Map predicts that perceptions of competence predict passive (e.g., covert, less intense, avoidant) rather than active (e.g., direct, explicit, overt) behaviors (Cuddy et al, 2007(Cuddy et al, , 2008.…”
Section: Linking the Scm To Discriminatory Behavior Toward Individualmentioning
confidence: 99%
“…The level of perceived competence will predict whether these passive behaviors are harmful or facilitative. Harmful behaviors include those that lead to detrimental outcomes for outgroups, whereas facilitative behaviors include those that lead to favorable outcomes for outgroups (Cuddy et al, 2007).…”
Section: Linking the Scm To Discriminatory Behavior Toward Individualmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggression: Zizzo (2003). Survey responses: Cuddy, et al (2007). that follows here might also be applied to similar forms of institutionalized envy.…”
Section: The Economics Of Peace and Security Journal Issn 1749-852xmentioning
confidence: 99%